Peningkatan Aktifitas dan Hasil Belajar Mapel IPS Melalui Model Pembelajaran Kooperatif Tipe Jigsaw pada Siswa Kelas VIII SMP - Sudarna (Cakrawala: Jurnal Pendidikan, 2018)
This study departs from the reality in SMP Negeri 1 Pangkah, at the beginning of the even semester of the Lesson Year 2016/2017 the results of learning IPS Class VIII H has not achieved the expected results due to low student learning outcomes in the subjects of social studies shown by the fact the lack of student learning activities in following the process IPS teaching and learning activities in the classroom. From the results of data analysis, stated: 1). Initial conditions, that the classical absorption that is the result of learning of all students only reaches 43.33% means it is under the provisions that have been set at 75% (ideal conditions). 2). In Cycle 1, that classical absorption reaches 66.67% which means still under the completeness of the class. 3). In Cycle 2, that the classical absorption reaches 83.33% is above the completeness of the class that has been determined